Os sentidos da/na educação superior enquanto potencializadores da aprendizagem de estudantes dos meios populares como proposta de educação no Brasil - Santos, Jane Kelly de Freitas (2023)
This thesis investigates the “meanings” attributed and constructed by students from popular backgrounds in and for Higher Education. With that aim, it highlights how much these “meanings” make a difference in the teaching and learning processes in relation to knowledge and mobilization of those students. The “meaning”, in Bernard Charlot’s understanding (2000, 2001, 2002, 2005, 2006, 2009, 2013) and in the authors’ understanding, who are also based on Historical-Cultural theory, goes beyond the significance, once the understanding of several natural factors of humanity also has meanings. “Meanings” are cultural, external, but are also present in each individual. Yet, even though permeated by external cultural actions of society, the social relations attribute “meaning” to the individuals’ activities, being meaning, thus, subjective and particular to each subject. Historically, and making the due relations of this thesis with the research line it is linked with - Educational Policies, of UPF Postgraduation Program in Education -, it is understood the progress concerning students’ access to Higher Education - the expansion process through democratization programs, such as ProUni and FIES-, have been evidenced by the existing literature. However, the numbers that portray dropout continue to be high and show that the performance of students from the most popular backgrounds is still inferior when compared to groups from higher social class. The present thesis is not centered in students from popular classes’ access to Higher Education, but in permanence (quality of learning) and conclusion. The research question, thus, is delimited as follows: Which “meanings” constructed and attributed by Higher Education students from popular backgrounds can enhance and enable better development in terms of learning, successful completion and good performance in educational activities in class and outside class? It is worth to point out that young students from popular backgrounds who achieve success in their student careers may be able to obtain subsidies (mobilizing “meanings” for establishing knowledge relations) for mobility and social transformation. Such understanding is necessary for the development of countries that consolidate social justice and equity in their systems and constitutes the social justification for the theme of this thesis. It is argued that it is essential to understand what the “meanings” of Higher Education are for these students, and the need to institutionalize actions that enhance their learning (permanence), in order to be reflected in the completion of the higher education course and in social mobilization (work in their fields of specialization, continue their studies, etc.). The research methodology used is qualitative, consisting of semi-structured interviews carried out with ProUni scholarship students in their last year of higher education at a community institution in the South of Brazil. The content of the interviews was analyzed and interpreted with the help of discursive practices and in light of the theory of sociology of the subject proposed by Bernard Charlot in his research. In all the interviewees' narratives it was possible to visualize the importance given to knowledge, learning processes and education. Professional learning, linked to doing and practicing specific to the chosen field of activity, stood out. All students considered such knowledge to be of great relevance to their work and attributed and constructed, during their training, “meanings” that mobilized them towards building relationships with knowledge. Furthermore, armed with these appropriations, they boosted their student performance and, possibly, their social mobility. In short, the study showed that understanding the “meaning” of Higher Education and the “meanings” constructed in the students’ trajectory can be a strong support in the development of institutional policies and programs that prioritize quality learning, graduation completion and mobilization of students from popular backgrounds